Enzymolysis of Azolla pinnata protein concentrate: effect of protease types and hydrolysis extents on the physicochemical, techno-functional and biological properties - Qoms, Mohammed S.; Arulrajah, Brisha; Shamsudin, Rosnah; Ramli, Nurul Shazini; Wan Ibadullah, Wan Zunairah; Chau, De-Ming; Saari, Nazamid (Elsevier, 2023)
Azolla pinnata is an underutilised fern and has been found to be a highly promising and sustainable source, making it a potential new plant-based protein source that can be used as a functional food ingredient. Therefore, the present work produced Azolla pinnata fern protein concentrate (AFPC) through alkaline solubilisation with isoelectric precipitation and investigated the effect of different proteases at varying degree of hydrolysis (DH) on the physicochemical, techno-functional properties and biological activities of Azolla fern protein hydrolysates. Enzymolysis with all proteases decreased the hydrophobicity, denaturation temperature and secondary structures (²-sheet and ±-helix) as the DH increased. Furthermore, the techno-functional properties including water and oil holding capacities, emulsion properties and foam stability were significantly reduced with increasing the DH, except for solubility and foaming capacity. Additionally, the pH had a positive correlation with all the techno-functional properties, except for water holding capacity. Hydrolysis with all proteases had a positive effect on the antioxidant and antibacterial activities. The partially hydrolysed protein with alcalase showed excellent techno-functional and antioxidant properties, while excellent antibacterial activity was observed for hydrolysate produced by flavourzyme under extensive hydrolysis. The current findings pave the way for the application of Azolla fern protein hydrolysates as promising and sustainable plant-based peptide to be utilised as nutraceutical and functional food ingredients.